Peningkatkan Ketrampilan Mitra dalam Internet Marketing Melalui Penerapan Internet of Things pada Industri Kopi Tanjung Java - Joko Minardi; Gunawan Mohammad (Abdimas Universal, 2023)
The Tanjung Village of  Jepara Regency is located on the slopes of Muria Mountain. Most of the livelihood of the villagers is farming. one of the plants that are suitable to be planted in this area besides rice is coffee. Most of the residents grow coffee only for personal consumption and not for sale. This is because the selling price is cheaper. The partner we invite to cooperate in this service activity is Tanjung Java Coffee. It was initiated by Mr. Nor Rokhim in 2018 with 5 employees. Previously in Tanjung Village, there was no coffee business so Tanjung Java coffee was a pioneer who started a coffee business there. The Partners Had problems are 1) at the roasting steps still using the 2nd party so that the roasting cost is expensive, 2) Marketing is still manual with a consignment system and offers to coffee shops in Jepara. Solutions to overcome these problems are through socialization methods, IoT and internet marketing training, application of roasting equipment and training on layout, mentoring, evaluation and monitoring. The results of this activity benefit partners by increasing the production capacity 33%, assets 60%, benefits 2%, and skills partners.